Investigation of the usability of biodiesel obtained from residual frying oil in a diesel engine with thermal barrier coating - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study, biofuel was produced from residual frying oil of cottonseed and D2, B5 and B100 fuels were prepared in order to use in experiments. These fuels were tested in a single cylinder, four strokes, 3 LD 510 model Lombardini Cl engine. Then the top surfaces of the piston and valves were coated with plasma spray coating method by using 100 p.m of NiCrAl as lining layer and over this layer the same surfaces were coated with 400 gm of the mixture that consists of %88 Zr02, %4 MgO and %8 Al203. After the coating process, above mentioned fuels were tested in the coated engine. Previously, same fuels had been tested in uncoated engine, at full load and various speeds. Performance, emission and combustion experiments were carried out in coated engine. By coating process, partial increases were observed in power, exhaust manifold temperature and engine noise, while partial decreases were seen in brake specific fuel consumption (Bsfc). Besides, partial reductions were found in carbon monoxide (CO), hydrocarbon (HC) and smoke opacity emissions, but partial increases were observed in nitrogen oxide (NO) emissions. Cylinder gas pressure values were higher for coated engine. Moreover, heat releases were close to each other in both engines. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Engine coating; LHR; Combustion; Diesel engine; EMISSION CHARACTERISTICS; EXHAUST EMISSIONS; NOX EMISSIONS; PERFORMANCE; COMBUSTION; FUEL